Pengaruh Konservatisme Akuntansi, Asimetri Informasi, Dan Perilaku Oportunistik Terhadap Nilai Perusahaan Dengan Kebijakan Deviden Sebagai Variabel Intervening - Marsyalova Yasmin; Nera Marinda Machdar (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research discusses the impact of accounting conservatism, information asymmetry, and opportunistic behavior on company value, with dividend policy acting as an intervening variable. The main objective of this research is to examine the positive influence of accounting conservatism, information asymmetry and opportunistic behavior on firm value, as well as to investigate the positive impact of dividend policy indirectly on the relationship between accounting conservatism, information asymmetry and opportunistic behavior. This research is quantitative, with the use of secondary data as the type of data used. The population that is the focus of this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the 2015-2022 period. The results of the analysis show that accounting conservatism has a positive impact on company value, as does information asymmetry and opportunistic behavior. Apart from that, dividend policy also has a positive impact on company value and can influence the relationship between accounting conservatism, information asymmetry and opportunistic behavior.